The impact of the implementation of single exit pricing for pharmaceuticals in South Africa - Pretorius, Daleen (My University, 2014)
ABSTRACT Pricing regulations have been implemented within the pharmaceutical industry in South Africa to ensure improved access to healthcare. The implementation of the Single Exit Price (SEP) effectively meant that the private pharmaceutical sector had to adjust from a free to a regulated market, where prices had to be cut and discounts discarded. The pricing structure changed to a transparent structure. These price ceilings resulted into a decrease in gross profit margins within independent, group and hospital pharmacies in the private healthcare sector. The aim of this research was to explore the impact of the implementation of SEP for pharmaceuticals in the private sector in South Africa through considering consistent pricing benefits to the patients as well as the changes in the business environment for retail pharmacies. A mixed methodology approach was pursued, using both quantitative and qualitative data analysis. A specific and actual price was obtained for certain medicines from 50 pharmacies to determine if consistent pricing benefits were experienced by patients through the introduction of SEP. This construed the quantitative data. In addition to this, 22 semi-structured interviews were conducted with pharmacy managers from independent, group and hospital pharmacies to determine the changes in the business environment following the introduction of SEP. The qualitative data obtained was analysed from a thematic perspective. Key findings from the research were that consistent pricing benefits were not realised to patients following the introduction of pricing regulations, and specifically SEP. Changes in the business environment of private retail pharmacies, following the introduction of SEP included: strategic changes, survival tactics and day to day changes as well as restructuring. Pricing regulation may initially seem to only have a positive impact on all stakeholders involved. However upon closer investigation the true impact of interference may be more harmful to all stakeholders in the long run.
MBA Thesis 2011
Keywords: Pharmaceutical industry -- South Africa.; Drugs -- Prices -- South Africa